2017
DOI: 10.5114/jcb.2017.68519
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography-based treatment planning for high-dose-rate brachytherapy using the tandem and ring applicator: influence of applicator choice on organ dose and inter-fraction adaptive planning

Abstract: Three dimensional planning for high-dose-rate (HDR) brachytherapy in cervical cancer has been highly recommended by consensus guidelines such as the American Brachytherapy Society (ABS) and the Groupe Européen de Curiethérapie – European Society for Radiotherapy and Oncology (GEC-ESTRO). In this document, we describe our experience with computed tomography (CT)-based planning using the tandem/ring applicator. We discuss the influence of applicator geometry on doses to organs at risk (OARs), namely the bladder,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The evolution of 3D planning from 2D planning resulted in the advent of volume-based HDR-BT planning, where the dose can be prescribed to the HR-CTV delineated by CT and/or MRI scans with close monitoring of OAR doses [ 7 , 8 ]. Accurate target and OAR delineation led to T&R and T&O based dose optimization techniques to create conformal plans by altering dwell times and dwell positions [ 34 , 35 , 36 ]. Several studies have shown the benefits of image-guided volume-based brachytherapy planning in gynecological malignancies compared to Point A-based plans [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evolution of 3D planning from 2D planning resulted in the advent of volume-based HDR-BT planning, where the dose can be prescribed to the HR-CTV delineated by CT and/or MRI scans with close monitoring of OAR doses [ 7 , 8 ]. Accurate target and OAR delineation led to T&R and T&O based dose optimization techniques to create conformal plans by altering dwell times and dwell positions [ 34 , 35 , 36 ]. Several studies have shown the benefits of image-guided volume-based brachytherapy planning in gynecological malignancies compared to Point A-based plans [ 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The decision can be easily made after the image registration of two CT images. Alternative way to reduce the dose to the critical organ are to place vaginal packing and/or rectal paddle to increase the distance between the radioactive source and the OARs, or modify the applicator angle and ring diameter for the last treatment to reduce the doses to the OARs, as proposed by …”
Section: Discussionmentioning
confidence: 99%
“…The entire radiation treatment is typically delivered in 45 Gy for 25 fractions with EBRT followed by HDR in 4–6 fractions using the tandem and ring (T&R) or tandem and ovoid (T&O) applicators. Magnetic resonance imaging or computerized tomography (CT) are currently used in HDR treatment planning to define the applicator position and delineate the target and organs at risk (OARs).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, if such displacement occurs intra-fractionally, one should expect dose variation of similar magnitude as well as shown by some recent studies [ 15 , 16 ]. Some studies have looked into the geometric displacement, anatomic change, and other effect in each fraction of image-guided brachytherapy [ 17 , 18 , 19 , 20 , 21 ]. Monitoring of applicator motion relative to patient is therefore important in MR/CT-guided HDR brachytherapy.…”
Section: Purposementioning
confidence: 99%